Propriedades estruturais e vibracionais dos fármacos captopril e risperidona sob condições extremas - Vasconcelos, Daniel Linhares Militão (2021)
In this study, we performed a vibrational and structural study of medicines captopril (C9H15NO3S) and risperidone (C23H27FN4O2). Captopril was the first anti-hypertensive medicine of the ACE inhibitor type, while risperidone is an atypical antipsychotic used in the treatment of schizophrenia. For this study, DFT calculations and experimental Raman spectroscopy techniques were used in extreme conditions of temperature and pressure. For captopril, DFT calculations were used to study the molecular conformation by rotating the dihedral angle ω (O4C18N6C15) in two environments, searching for the lower energy structures. This allowed the calculation of the energies of the frontier orbitals (HOMO and LUMO) and to find the lectrostatic potential surfaces for the structures obtained. The study showed that, although less stable, the cis conformation of captopril present ligand orbitals and possibles sities of nucleophilic and electrophilic attack similar to the trans conformation. After obtaining the lowest energy molecular structure, we calculated the theoretical vibrational spectrum and the assignment of the normal modes. The theoretical spectra of both captopril and risperidone showed a good agreement with the experimental spectra, allowing the identification of the vibrational modes according to the PED (potential energy distribution) values. The Raman experiments on captopril for pressures up to 6.7 GPa indicate the occurrence of a structural phase transition between 2 and 3 GPa. Before the transition, the C-O stretching modes decrease their wavenumbers, however, after the transition the modes shift to higher wavenumbers, suggesting an increase in the length of the hydrogen bond related to the oxygen atoms. For captopril, we performed studies varying the temperature from 300 to 8 K and from 300 to 375K. In both experiments no structural phase transition was observed. However, in the Raman experiments at low temperature, some changes were observed in the modes that are related to atoms that participates of hydrogen bonds, indicating that the captopril may have undergone a conformational change during the cooling. In none of the three experiments carried out on captopril was observed a conformational change from trans to cis. Risperidone was investigated for pressures up to 6.7 GPa. The Raman spectra points to a phase transition between 0.6 and 0.9 GPa. Changes in the vibrational modes associated with several regions of the molecule indicate that the transition involves a complex conformational change as well as the hydrogen bond formed by the atom O26.